PERGESERAN ADAT PERKAWINAN MASYARAKAT MELAYU DI DESA TELUK MEGA KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Desi Susanti; Drs. Kamaruddin, M.Si '; Bunari, S.Pd,M.Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The customs are rules of conduct adopted hereditary and is valid for a long time that are tight and binding. Customs in a very diverse nation one of the customs of the Malay society is marriage, which has rules and regulations that have been determined by local custom. Marriage customs in Malay culture impressed umit as many stages through. In pekawinan traditional Malay ceremony conducted a series of detailed and neatly arranged all of which must be done by the bride and groom couples and families. The purpose of this study is to investigate the implementation of customary marriages Malay community in Teluk Mega Tanah Putih Rokan Hilir, to determine the forms and effects of shifting marriage customs Malay community in Teluk Mega Tanah Putih Rokan Hilir, to determine the factors that causing a shift in the customary marriage Malay community in Teluk Mega Tanah Putih Rokan Hilir, to know the business community in maintaining and preserving traditional marriage Malay community in Teluk Mega Tanah Putih Rokan Hilir. he method used is qualitative descriptive, where data were collected through observation, interviews, literature study, and documentation. Data was analyzed using qualitative way. The research locations namely Teluk Mega Tanah Putih Rokan Hilir. The research was conducted on the seminar proposal to the thesis examination. The results showed that the procedure of marriage customs Malay community in Teluk Mega still performed up to now. However, there are procedures for marriage customs are experiencing a shift in its implementation. Factors that cause a shift is technological progress, economic factors, modernization, renewal between cross/interbreeding and globalization. Enterprises Malay community in Teluk Mega play a huge role in addressing and improving the traditinal practices that shift.Key Words: Shift, Indigenous, Marriage